Sweatshops, Harm and Exploitation: A Proposal to Operationalise the Model of Structural Injustice - Corvino, Fausto (Conatus - Journal of Philosophy, 2020)
In this article, I firstly discuss the person-affecting view of harm, distinguishing between the liability and the structural models of responsibility, and also explaining why it is unsatisfactory, from a moral point of view, to interpret a given harm as a loss with respect to a diachronic baseline. Then, I take sweatshops as an example and I entertain two further issues that are related to the assessment of harm and that are necessary for operationalising a comprehensive model of responsibility, that takes into account both liability and structural injustice. The first one is how to interpret harm when it is coexistent with a diachronic benefit and/or the parties involved in the social structures leading to harm seek to unload their responsibility by hiding behind a cooperative deadlock. The second one is how far along the chain of actions leading to harm can structural responsibility be extended.